An Investigation of BBC Learning English for Listening Tasks in a Computerized Academic - Mega Witjaksana; Sholihatul Hamidah Daulay (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
This research aimed to investigate the impact of the BBC Learning English application on listening skills among 10th-grade students in a computerized academic setting. The study involved 46 students from MAS TPI Sawit Seberang, divided into two groups of 23 students each. The experimental group utilized the BBC Learning English application, while the control group received traditional instruction. Employing a quasi-experimental design with pre-tests and post-tests, the experimental group also completed a questionnaire. Statistical analysis revealed significant differences (α = 0.05) in post-test listening scores, favoring the experimental group. Additionally,